Transport-radiation feedbacks of ozone in the tropical tropopause layer - Charlesworth, Edward, author; Birner, Thomas, advisor; Ravishankara, A. R., committee member; Oprea, Iuliana, committee member (Colorado State University. Libraries, 2017)
The tropical tropopause layer (TTL) is a region in the atmosphere that shows an interesting combination of tropospheric and stratospheric characteristics over the extent of several kilometers. For example, the TTL shows both convectively-driven tropospheric dynamics and the beginning of the mechanically-driven Brewer-Dobson circulation. The TTL is also important for climate due to its role as the gateway for most air that enters the stratosphere. In this work, a single-column model is used to investigate why a tropical tropopause layer of the observed vertical extent exists. This is done through computations of radiative convective equilibrium temperatures and interactive photochemical equilibrium ozone concentrations. The model uses only a basic simulation of ozone chemistry, convection, and stratospheric upwelling, but the results show that such a simplified expression of critical processes can produce temperature and ozone profiles that are very similar to observations. It is found that vertical transport of ozone by the Brewer-Dobson circulation and its associated effects on radiative heating rates is of first-order importance in producing the observed temperature structure of the tropical tropopause layer, within this simple modeling context. Adiabatic cooling due to stratospheric upwelling is found to be equally important to generate the tropical tropopause layer. With these combined processes, it is suggested that the even the lowest upwelling velocities on the order of observed upwelling can produce a TTL. With regards to climate change through the strengthening Brewer-Dobson circulation, this model suggests that an increase in upwelling from 0.5 to 0.6 mm/s should cool the cold point tropopause by 3.5 K and loft it by half a kilometer.
Keywords: dynamics; radiation; Brewer-Dobson circulation; tropical tropopause layer; ozone